Chapter Effect of Climate Change and anthropogenic pressures on the European eel Anguilla anguilla from RAMSAR Wetland Ichkeul Lake: prediction from the Random Forest model - Toujani, Rachid (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This study aims to assess the trophic level of Lake Ichkeul and predict the effect of climate change and anthropogenic pressures on European eel using the trophic index TRIX and the Random Forest RF model. The TRIX values show the poor water quality of the lake. While the RF model shows that eel landing depends on water level, turbidity, and salinity. The RF model gave an R2 =58.4% > R2 =40.3% from Multiple linear regression, confirming the high performance of the RF model. The combination of the two models is an appropriate approach to be used in decision making by civil authorities.